Modified Adaptive Chirplet Decomposition with Application in ISAR Imaging of Maneuvering Targets. (4th February 2009) - Wang Wang, Yong Yong; Jiang Jiang, Yi-Cheng Yi-Cheng
Abstract : The modified adaptive Chirplet decomposition (MACD) is presented in this paper. It is based on the extension of the traditional Chirplet atoms to the form of the quadratic frequency-modulated signals. The accuracy of the signal decomposition is improved compared with the traditional Chirplet decomposition. A practical algorithm for the parameters estimation of monocomponent MACD atom and the decomposition method based on the CLEAN technique to the multicomponent signals are proposed. Finally, this algorithm is used in the ISAR imaging of maneuvering targets, and the quality of ISAR images improves greatly. The results of real data and simulated data demonstrate the validity of the method proposed.